2020
DOI: 10.1186/s13063-019-3947-6
|View full text |Cite
|
Sign up to set email alerts
|

Initiate Danhong Injection before or after percutaneous coronary intervention for microvascular obstruction in ST-elevation myocardial infarction (DIRECTION): study protocol for a randomized controlled trial

Abstract: on behalf of the DIRECTION investigatorsAbstract Background: No treatment has convincingly been proven to be beneficial for microvascular obstruction (MVO) in patients with ST-elevation myocardial infarction (STEMI). Several studies have described the effects of Danhong Injection. However, evidence of a rigorously designed verification study is still lacking, and the intervention timing of Danhong Injection is uncertain. Methods:The DIRECTION study is a multicenter, prospective, randomized, evaluator-blind stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Studies had shown that salvianolic acid such as danshensu and salvianolic acid B had a protective effect on the heart of AMI, which was closely related to the inhibition of intracellular calcium pathways ( Chen et al, 2011 ; Wang et al, 2011 ; Zhao et al, 2012 ; Lin et al, 2016 ). In a cross-sectional study, Zhang et al, found that serum calcium concentrations were significantly lower in patients with first AMI compared with patients without AMI, further emphasizing the value of serum calcium level in clinical practice ( Zhang et al, 2020 ). Similarly, integrated bioinformatics studies revealed that the calcium signaling pathway plays an important role in AMI ( Guo et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies had shown that salvianolic acid such as danshensu and salvianolic acid B had a protective effect on the heart of AMI, which was closely related to the inhibition of intracellular calcium pathways ( Chen et al, 2011 ; Wang et al, 2011 ; Zhao et al, 2012 ; Lin et al, 2016 ). In a cross-sectional study, Zhang et al, found that serum calcium concentrations were significantly lower in patients with first AMI compared with patients without AMI, further emphasizing the value of serum calcium level in clinical practice ( Zhang et al, 2020 ). Similarly, integrated bioinformatics studies revealed that the calcium signaling pathway plays an important role in AMI ( Guo et al, 2021a ).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation and immune injury in SCAD have been proven (54), and whether Taoren Honghua Jian Granule (桃 仁 红 花 煎 颗 粒) could alleviate symptoms, control inflammation, and improve quality of life in patients with SCAD will also be explored (55). Other RCTs will reveal the efficacy and safety of Danhong Injection, as well as its optimal timing of intervention (before or after percutaneous coronary intervention) to prevent microvascular obstruction in patients with ST-segment elevation myocardial infarction (56), and determine the clinical efficacy and safety of traditional Chinese medicine Tongxinluo Capsule in the treatment of ST-segment elevation myocardial infarction patients in the reperfusion era (57).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of DHI in the perioperative period was previously assessed in a systematic review by Zhang et al, who concluded that DHI may improve reperfusion after PCI ( Zhang et al, 2020 ). After a meta-analysis of 1,131 patients in 12 studies, Yuan et al concluded that DHI can improve the perioperative cardiac function in patients with AMI and increase the TIMI blood flow grade ( Yuan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%